2022
DOI: 10.1108/manm-02-2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

I trust friends before I trust companies: The mediation of WOM and brand love on psychological contract fulfilment and repurchase intention

Abstract: PurposeConsumer psychology research has established the importance of customer satisfaction as a determinant of customer repurchasing intention. Nonetheless, even satisfied customers switch brands. Also, even dissatisfied customers have repurchasing intentions. This means that customer repurchasing behaviour is extremely difficult to predict, necessitating additional research to identify additional factors that can help organizations better understand the methods to predict customer repurchasing intention. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
22

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 59 publications
1
3
0
22
Order By: Relevance
“…Similarly, farmers with strong emotional relationships, common interests and similar likes and dislikes are more likely to deliver the message in a positive way. These findings are consistent with previous research (Cooley & Parks-Yancy, 2019; Ismail, 2022) which suggested that individuals can more likely trust friends they know, especially during making purchase decisions suggesting that individuals with prior knowledge and subjective experiences can better comprehend the topic before exposing the information to others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, farmers with strong emotional relationships, common interests and similar likes and dislikes are more likely to deliver the message in a positive way. These findings are consistent with previous research (Cooley & Parks-Yancy, 2019; Ismail, 2022) which suggested that individuals can more likely trust friends they know, especially during making purchase decisions suggesting that individuals with prior knowledge and subjective experiences can better comprehend the topic before exposing the information to others.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, the study provides a theoretical understanding of how WOM message delivery can mediate the relationship between WOM dimensions and market participation, highlighting the power of information from relatives and friends as a solution to misleading information from middlemen. Thirdly, this study fills a gap in the literature as previous studies on WOM have been mostly limited to other disciplines such as public procurement management (Ismail & Changalima, 2022), customer and marketing management (Ismail, 2022) and educational management (Amani, 2022), with little attention paid to smallholder farming and market participation. Lastly, this study contributes to the Maslow’ theory by postulating that smallholder farmers’ motivation to sell at marketplaces could stem from the need to generate income to fulfill their basic needs (shelter, healthcare, food), which aligns with the foundational level of Maslow's hierarchy.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Batra et al, (2012) asserted that it is important to acknowledge the distinction. There is considerable evidence that shows that brand love has a major influence on repurchase intention (Hsu, 2023;Ismail, 2022). Brand love has also been proven to have an impact on consumer forgiveness and attitude towards an extension.…”
Section: Brand Lovementioning
confidence: 99%
“…Berdasarkan kesan yang diberikan konsumen tentang Bengkel Mobil X, diketahui bahwa penyebaran informasi yang diberikan konsumen Bengkel Mobil X kepada orang lain menjadi alasan tertinggi yang mendorong konsumen lebih memilih untuk terus membeli sparepart atau menggunakan jasa service kendaraan dari Bengkel Mobil X. Kemudian diikuti oleh ajakan teman konsumen untuk menggunakan layanan service selain di Bengkel Mobil X, karena alasan sudah terbiasa melakukan service ditempat tersebut. Oleh karena itu, penelitian ini menggunakan model penelitian yang dikemukakan oleh Ismail (2022), dimana word of mouth (WOM) yang positif dan brand love ditemukan mampu memediasi hubungan kontrak psikologis dan Repurchase intention konsumen.…”
Section: Pendahuluanunclassified
“…Kontrak relational dalam komunitas sosial memengaruhi brand love, brand love memengaruhi word of mouth konsumen baik dalam lingkungan fisik maupun lingkungan online, sementara kontrak transactional terkait persepsi harga ditemukan tidak memengaruhi Repurchase intention konsumen (Nugroho et al, 2021). Sebagaimana telah dibuktikan dalam penelitian (Ismail, 2022) yang menemukan bahwa brand love memiliki kemampuan dalam memediasi hubungan kontrak psikologi dengan Repurchase intention konsumen. Di sisi lain, kontrak psikologis relational memiliki peran besar dalam memengaruhi penyebaran Positive Word of mouth tentang perusahaan baik terkait harga atau kemampuan karyawan dalam memberikan layanan.…”
Section: Pendahuluanunclassified